To study the viability of Rras Bakti (M) Sdn.Bhd adopting its own distribution channel / Mohd Abidzar Zainol Abidin - Zainol Abidin, Mohd Abidzar (Faculty of Business and Management, 2009)
Manufacturers face demand uncertainty and new retailing practices, such traditional outsourcing activities thus it become their additional cost of doing business. These situation mainly reflects to the downturn economic condition, because this tense situation, the used of intermediaries or channel of distribution become one of major cost to them. They think that they must either perpetuate the intermediaries or eliminate it. This research study to see whether the intermediaries’ can increase the company profit and sale or it is better if the company has its own marketing team. I try to generate ideas of creating possible solution whether to use intermediaries as a channel of distribution or adopting their own distribution channel. Intermediaries in other words can be best describing as outsource providers. However, the company call themselves as an agent to supply the product to their client. In this study, I choose to look of how the achievement, performance and effort of intermediaries as an agent can increase the sale volume of Rras Bakti (M) Sdn.Bhd product. In this study, performance channel of distribution is defined as the degree to which the channel of distribution alliance partner engages in behavior that contributes to the fulfillment of the manufacturer's objectives.